Employment Effects of Restricting Fixed-Term Contracts: Theory and Evidence - Pierre Cahuc; Pauline Carry; Franck Malherbet; Pedro S. Martins (Institute of Labor Economics (IZA), 2022)
This paper examines a labor law reform implemented in Portugal in 2009 which restricted the use of fixed-term contracts to reduce labor market segmentation. The reform targeted establishments created by large firms above a specific size threshold, covering about 15% of total employment. Drawing on linked employer-employee longitudinal data and regression discontinuity methods, we find that, while the reform was successful in reducing the number of fixed-term jobs, it did not increase the number of permanent contracts and decreased employment in large firms. However, we find evidence of positive spillovers to small firms that may bias reduced form estimates. To evaluate general equilibrium effects, we build and estimate a directed search and matching model with endogenous number of establishments and jobs. We find spillover effects that induce small biases on reduced form estimates but that significantly change the evaluation of the overall impact of the reform because they diffuse to the whole economy. We estimate that the reform slightly reduced aggregate employment and had negative effects on the welfare of employees and unemployed workers.
Keywords: J23; J41; J63; 330; directed search and matching; labor market segmentation; regression discontinuity